ChemInform Abstract: Nitridomagnesosilicate Ba[Mg3SiN4]:Eu2+ and Structure—Property Relations of Similar Narrow‐Band Red Nitride Phosphors. Issue 21 (May 2015) - Schmiechen, Sebastian; Strobel, Philipp; Hecht, Cora; Reith, Thomas; Siegert, Markus; Schmidt, Peter J.; Huppertz, Petra; Wiechert, Detlef; Schnick, Wolfgang
Abstract Ba[Mg3SiN4]:Eux (x = 0.005‐0.025) is prepared by a solid state metathesis reaction of BaF2, Mg3N2, Si(NH)2, LiN3 as N source, Li as flux, and EuF3 as dopant (Ta tube in evacuated silica tube, 1050 °C, 24 h; cooling to 500 °C within 250 h).